Pengembangan Civic Skill Melalui Projek Penguatan Profil Pelajar Pancasila (P5) Berbasis Kearifan Lokal Batik Banten pada Peserta didik di SMP Negeri 1 Kota Serang - Roudatus Solihah; Candra Viamita Prakoso; Wiwin Purwinarti; Lukman Hidayat (Universitas Palan, 2025)
This study aims to describe the Development of Civic Skills Through the Pancasila Student Profile Strengthening Project (P5) Based on Banten Batik Local Wisdom for Students at SMPN 1 Serang City. This study uses a quantitative approach and a descriptive approach. Practical activities carried out, such as batik making and exhibitions, provide direct experience that improves students' communication, cooperation, and leadership skills. This study found that the integration of local wisdom in learning can develop students' civic skills, build a sense of social responsibility, and increase awareness of the importance of active participation in society. The results of this study describe that in the implementation of the Pancasila Student Profile Strengthening Project (P5) Based on Banten Batik Local Wisdom consisting of three stages, namely planning, implementation, and evaluation, SMPN 1 Serang City has implemented Civic Skills.